STRATEGIC BUSINESS ANALYSIS USING SWOT METHODS TO IMPROVE BRAND COMPETITIVENESS - Azzahra, Aretha Belva; Khalid , Zulvia (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Lite n' Easy is one of the healthy food companies in Australia, Lite n’ Easy must continue to grow in this difficult business climate. Therefore, finding growth opportunities is essential. This study uses a combination of SWOT and STP analysis to find business growth possibilities. Market segmentation, target market, and market position were all examined using STP analysis. Strengths, Weaknesses, Opportunities, and Threats (SWOT) are the elements of the company's internal and external environment that are examined in the SWOT analysis. Through the integration of both analyses, this study provides a reliable approach to determining prospective areas for expansion. The results show that the application of SWOT analysis and STP can improve strategic planning and provide a comprehensive viewpoint to capitalize on new opportunities.